Prinsip Dasar Perbankan Syariah - Maimun, Maimun; Tzahira, Dara (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2022)
Principles in banking are important as the basis that can be used as a basis for thinking related to muamalah and all transactions in the world of Islamic banking. The basic principles of sharia banking are the principles of free maghrib (maysir, gharar, haram, usury, and batil), trust and prudence in the management of sharia banking activities, and principles based on contracts. These three principles refer to Islamic sharia by referring to the Qur'an and Hadith so that they must be implemented in various activities.